Marek Hłasko i „Trybuna Ludu” - Młynarczyk, Radoslaw (Załącznik Kulturoznawczy, 2024)
The article analyzes 4 texts – mini-articles – which Marek Hłasko wrote for “Trybuna Ludu” (en. “People’s Tribune”), the most popular post-war Polish daily newspaper, while working as a driver. The texts were presented against the background of similar reports from construction sites of Polish People’s Republic, written by workers from all over the country. In almost every issue of the newspaper, short contributions by amateur authors appeared, which often took the form of denunciations. An attempt was made to classify the field correspondences genologically, trying to establish their place in the history of Polish literature, determine their literary or journalistic quality. Various categories were applied to settle the dispute: individual style, the perspective of the sender and the recipient model, authorial intentions. Finally, an attempt was made to establish whether it is possible to speak of the individual, separate character of the texts created by Hłasko and his responsibility for the written content, and whether those short texts can be treated as his first literary attempts.